2017
DOI: 10.1063/1.4985582
|View full text |Cite
|
Sign up to set email alerts
|

AlN/Pt/LN structure for SAW sensors capable of operating at high temperature

Abstract: There is a need for wireless sensors able to operate in the intermediate temperature range (ITR) between 300 °C and 600 °C. Surface acoustic wave (SAW) sensors are promising candidates to solve this issue. However, existing SAW sensors most often fail in the ITR, due to the quick degradation of the sensor housing in extreme conditions. A promising way to circumvent the issue is to use “package-less” devices, where the acoustic waves are guided in a multilayered structure where they are intrinsically protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…However, it has a number of limitations, the most important being the excessive damping (propagation losses) of surface waves when the operating frequency exceeds 1 GHz [15]. Recently, efforts have been devoted to the development of a SAW sensor heterostructure for high and very high temperature applications such as AlN/Pt/LiNbO 3 [16] and AlN/Sapphire [17][18][19][20][21]. The AlN/Sapphire SAW structure can also operate at very high frequencies [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has a number of limitations, the most important being the excessive damping (propagation losses) of surface waves when the operating frequency exceeds 1 GHz [15]. Recently, efforts have been devoted to the development of a SAW sensor heterostructure for high and very high temperature applications such as AlN/Pt/LiNbO 3 [16] and AlN/Sapphire [17][18][19][20][21]. The AlN/Sapphire SAW structure can also operate at very high frequencies [18].…”
Section: Introductionmentioning
confidence: 99%
“…LGS also has many restrictions such as low surface acoustic velocity and increasing acoustic propagation losses with the temperature at higher frequency [9]. Compared with the former two, aluminum nitride (AlN) exhibits higher surface wave velocity (5607 m/s) [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, YCOB suffers from the pyroelectric effect, and its surface is easy to absorb impurities in the environment at high temperature, which causes severe degradation of device performance. LGS also has many restrictions such as low surface acoustic velocity and increasing acoustic propagation losses with the temperature at higher frequency [ 9 ]. Compared with the former two, aluminum nitride (AlN) exhibits higher surface wave velocity (5607 m/s) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…the human body. To eliminate this bottleneck, some authors have suggested a bilayer structure with AlN and LiNbO3 128° Y-cut [8]. The confinement of the energy is possible due to the use of heavy metal electrodes (Pt) and occurs mostly owing to specific properties of LiNbO3 128° Y-cut which shows a decoupling between Rayleigh modes and Shear Horizontal modes.…”
Section: Introductionmentioning
confidence: 99%